2010
DOI: 10.1007/s11064-010-0295-z
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Damage in Rat Brain During Aging: Interplay Between Energy and Metabolic Key Target Proteins

Abstract: Aging is characterized by a gradual and continuous loss of physiological functions and responses particularly marked in the central nervous system. Reactive oxygen species (ROS) can react with all major biological macromolecules such as carbohydrates, nucleic acids, lipids, and proteins. Since proteins are the major components of biological systems and regulate multiple cellular pathways, oxidative damage of key proteins are considered to be the principal molecular mechanisms leading to age-related deficits. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 57 publications
1
25
0
2
Order By: Relevance
“…However, it is likely that the antioxidant properties of the extract played an important role. This proposition bases on the fact that many alterations in enzymatic activities in the brain of old rats are accompanied by oxidative modifications in proteins such as carbonylations and nitrations [67]. In principle such modifications can be prevented by improving the antioxidant defenses of the cells, a task for which the A. blazei extract is well equipped as already discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is likely that the antioxidant properties of the extract played an important role. This proposition bases on the fact that many alterations in enzymatic activities in the brain of old rats are accompanied by oxidative modifications in proteins such as carbonylations and nitrations [67]. In principle such modifications can be prevented by improving the antioxidant defenses of the cells, a task for which the A. blazei extract is well equipped as already discussed above.…”
Section: Discussionmentioning
confidence: 99%
“…I mpaired bioenergetics and mitochondria metabolism, together with oxidative stress, are commonalities underlying age-related neurodegenerative diseases, such as Parkinson's (PD), Huntington's (HD) and Alzheimer's (AD) disease, Friedreich's ataxia, or amyotrophic lateral sclerosis (ALS), to cite a few (11,12,14,29,36,37,40). It has been postulated that oxidative stress in mitochondria can reduce the activities of their various proteins due to oxidative modifications (8,32,43,60,65).…”
Section: Introductionmentioning
confidence: 99%
“…It is also observed that proteins bearing the effects of ROS attack accumulate with age (Di Domenico et al, 2010). Thus, it is frequently assumed that attack by ROS is a cause of ageing and age-related proteotoxicity.…”
Section: Introductionmentioning
confidence: 99%